2018
DOI: 10.1037/hea0000634
|View full text |Cite
|
Sign up to set email alerts
|

Unpredictability, body awareness, and eating in the absence of hunger: A cognitive schemas approach.

Abstract: These results suggest that having an unpredictability schema may be an important predictor of low body awareness and eating in the absence of hunger. Although eating in the absence of hunger may have historically promoted survival in circumstances marked by unpredictability, they may contribute to obesity risk in contemporary food-rich environments. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 49 publications
0
18
0
1
Order By: Relevance
“…Another related weakness is using multi-informant reporting to measure internal states, as well as external environments, because individual differences in interoception may potentially be correlated with LH (e.g. [71]) and may in general confound the effects of body conditions. However, cognitive assessment of both internal and external information may become integral parts of human LH calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Another related weakness is using multi-informant reporting to measure internal states, as well as external environments, because individual differences in interoception may potentially be correlated with LH (e.g. [71]) and may in general confound the effects of body conditions. However, cognitive assessment of both internal and external information may become integral parts of human LH calibration.…”
Section: Discussionmentioning
confidence: 99%
“…Females also tend to have slower LHS characteristics than males (e.g., greater parental investment), similar to the pattern of sex differences seen in EA (Barrett et al, 2000; Ciarrochi et al, 2005; Wright et al, 2017). In addition, previous work has also linked LHS to both bodily/interoceptive awareness (Proffitt Leyva & Hill, 2018) and emotional intelligence (van der Linden et al, 2015), each of which have been linked to EA or the related construct of alexithymia (Aaron et al, 2020; Brewer et al, 2016; Herbert et al, 2011; Onur et al, 2013; Pollatos et al, 2005; Simmons et al, 2013; Smith, Lane, et al, 2018; Terasawa et al, 2014; Trevisan et al, 2019; Zaki et al, 2012). For example, Proffitt Leyva and Hill (2018) have suggested that individuals may develop low interoceptive awareness because they selectively allocate energy resources toward monitoring the conditions in the external environment, and therefore fail to monitor and learn from internal bodily and emotional states.…”
mentioning
confidence: 99%
“…One possible mechanism that considers the environment is that individuals lower in the social hierarchy have access to fewer social resources and experience more social unpredictability, further contributing to chronic stress [59]. Past studies indicated that unpredictability schemas, including those related to neighborhood quality, contribute to dysregulated eating [60]. Another potential explanation accounts for neurobiological pathways involved in consuming high-calorie foods.…”
Section: Discussionmentioning
confidence: 99%